Absorption and translocation of [14C]2,4-dichlorophenoxyacetic acid in herbicide-tolerant chromosome substitution lines of Gossypium hirsutum L - Perez, Loida M.; Yue, Ziming; Saha, Sukumar; Dean, Jeffrey F. D.; Jenkins, Johnie N.; Stelly, David M.; Tseng, Te-Ming (Frontiers in Agronomy, 2022)
Upland cotton is sensitive to 2,4-dichlorophenoxyacetic acid (2,4-D), and spray drift from adjacent crops can cause yield loss. Identifying potentially 2,4-D tolerant cotton chromosome substitution (CS) lines with well-characterized tolerance mechanisms could provide a significant step into the development and genetic improvement of upland cotton. Experiments were conducted to understand the possible mechanism of herbicide tolerance in CS-T04-15, CS-T07, and CS-B15sh, 2,4-D herbicide-tolerant cotton CS lines compared with TM-1, the 2,4-D herbicide susceptible recurrent parent of the CS line. Using [14C]2,4-D, the percent absorption rate and translocation patterns of the 14C-labeled herbicide at 6 to 48 h after treatment (HAT) were determined. The tolerant cotton CS lines showed 15-19% [14C]2,4-D uptake, while TM-1 exhibited a reduced uptake of only 1.4% [14C]2,4-D at 24 HAT. Distribution of the absorbed [14C]2,4-D showed that 2-5% was translocated outside the treated leaf in the tolerant CS lines. In contrast, 77% of the herbicide was translocated above and below the treated leaf in line TM-1. Interestingly, CS-T04-15 showed a restricted movement of 14C below the treated leaf at 6 to 48 HAT, suggesting novel information on mechanisms of herbicide tolerance to 2,4-D in cotton. This finding is the first report on upland cotton demonstrating a complex differential uptake and translocation associated with herbicide tolerance for [14C]2,4-D in cotton CS lines.